Analisis Manajemen Persediaan Bahan Baku Cokelat Pada Rapoviaka Simple - Ainung Ainung; Asngadi Asngadi; Syamsuddin Syamsuddin; Wiri Wirastuti (Journal Economic Excellence Ibnu Sina, 2024)
This study aims to conduct an in-depth analysis of chocolate raw material inventory management at Rapoviaka Simple, a chocolate company operating at Jalan Perumahan Dosen, Blok B4 No 2, Central Sulawesi.  The research method used is the Economic Order Quantity (EOQ) method to assess and improve the inventory management process. By using interviews, observations, and analysis of internal company documents, an in-depth understanding of the existing practices and challenges faced by Rapoviaka Simple was obtained.  The results of this study are expected to provide useful insights for similar companies and contribute to the inventory management literature in the context of the food and beverage industry.